Does pre‐eclampsia without proteinuria lead to different pregnancy outcomes than pre‐eclampsia with proteinuria?. Issue 8 (1st July 2019) - Tochio, Azusa; Obata, Soichiro; Saigusa, Yusuke; Shindo, Ryosuke; Miyagi, Etsuko; Aoki, Shigeru
Abstract: Aims: The Japanese Society for the Study of Hypertension in Pregnancy revised the diagnostic criteria for pre‐eclampsia (PE) to conform to those of the International Society for the Study of Hypertension in Pregnancy (ISSHP) in 2018. This study aimed to investigate whether pregnancy outcomes differ based on the presence of proteinuria and validate the adoption of the ISSHP criteria in Japan. Methods: This is a retrospective study involving 308 women diagnosed with hypertensive disorders of pregnancy at a tertiary center. They were divided into the following groups: PE with proteinuria ( n = 218), PE without proteinuria ( n = 45) and gestational hypertension ( n = 45) according to the ISSHP criteria for comparison of pregnancy outcomes. Results: Applying the ISSHP criteria increased the number of pregnant women diagnosed as having PE by 14.6% (45 women). The difference in the rate of composite maternal complications between the two groups was unremarkable, with 33 cases (15.1%) in the PE with proteinuria group and 9 cases (20%) in the PE without proteinuria group. Moreover, composite neonatal complications occurred in 37 cases (17%) of PE with proteinuria group and 6 cases (13.3%) of PE without proteinuria group, showing remarkably similar incidence rate in the two groups. Women with PE with and without proteinuria had significantly earlier deliveries and lower neonatal birth weight than those with gestational hypertension. Conclusion: Pregnancy outcomes of PE with and without proteinuria were almost similar although their incidence increased, confirming its validity for adaptation of the ISSHP criteria in Japan.